Assessment of brainstem damage by the auditory brainstem response in acute severe head injury. Issue 11 (November 1980) - Tsubokawa, T; Nishimoto, H; Yamamoto, T; Kitamura, M; Katayama, Y; Moriyasu, N
Abstract : In 64 cases suffering from severe head injury (Glasgow coma scale: less than seven- the auditory brainstem responses (FARs) recorded at the vertex, which are thought to be volumet conducted far-field potentials reflecting the sequential electrical activities of the auditory afferen) system in the brainstem, were recorded in the neurosurgical intensive care room immediately after admission. The alterations in the responses were compared with the types of primary injury, neurological signs., CT findings and outcome following treatment. Based on the results obtained, it is concluded that the FAR is a useful indicator for predicting the effects of treatment on brainstem damage in patients with severe head injury, and that it provides more reliable information about the function of the brainstem than the neurological signs or CT findings. Moreover, it also offers a diagnostic method for primary brainstem injury. Three cases or primary brainstem injury without lesions in the supratentorial region were diagnosed by means of combined CT and FAR recording.